Public companies as subjects of private law relations in the Republic of Kazakhstan - Idrysheva, S.K.; Klimova, T.V. (Bulletin of the Karaganda University “Law Series”, 2020)
The purpose of the work is to consider the «public company» institute, which existed in the legislation on joint-stock companies of the Republic of Kazakhstan from 2007 to mid-2018, and justify the need to restore this type of corporation. Through a comparative legal analysis of the legislation and corporate practice of foreign countries, the article provides evidence of the need for this legal institution for Kazakhstan, which is consistent with the OECD principles, the Legal Policy Concept and the Message of the First President of the Republic of Kazakhstan on strengthening the institution of «public corporations» and introducing the principles of corporate governance of the OECD. As a result of comparing the institution of public companies with other legal entities of public law in Kazakhstan, the authors conclude that legal requirements are presented to legal entities only in terms of observing the transparency of financial statements. Having considered a significant list of by-laws of the Republic of Kazakhstan governing corporate relations in organizations with a predominant share of the state, it is concluded that the principles of OECD are mandatory for all corporate organizations, regardless of ownership, and that the principles of corporate governance are not fixed at the level of by-laws, but at the level of laws.